MENGURANGI PERILAKU MEROKOK PADA SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK - Nunuk Yuli Sulistyoningrum (Jurnal Penelitian Bimbingan dan Konseling, 2018)
This research aims to gain an overview of the extent to which the Group Guidance service can help reduce the smoking behavior. This research use approach Research Tindakah class (PTK). The subject of research is the grade 5 State JUNIOR IXC Tangerang. The results showed that: (1) smoking on the Behavior of students before treatmen indicates the level of smoking behaviour of students, i.e. 2 (33.33%) of 6 students behave the smoking medium, and 4 (66.67%) of 6 students behave smoke light, (2) The smoking behavior in students after the treatmen show 1 (16.67%) of 6 students behave and smoked 5 (83.33%) of 6 students behave smoke is low, but if viewed from the results of the questionnaire, the sixth field is the student experience the decrease against merokoknya behavior, (3) there is a significant difference between before the given service through the guidance of the Group and after the given service through the guidance of the group. Keywords: smoking; guidance group.